Radical Scavenging Activity, Brine Shrimp Lethality Assay and HPLC Analysis of Methanol Extracts of Secamone afzelii (Roem. & Schult.) K. Schum and Ceiba pentandra (Linn.) Gaertn. (Nigerian Journal of Pharmaceutical Research, 2022)
Background: Medicinal plants produce several phytochemicals with strong free radical scavenging activities.Objectives: To evaluate radical scavenging activity, brine shrimp toxicity and high-performance liquid chromatography (HPLC) analysis of the methanol extracts of Secamone afzelii (SA) leaves and Ceiba pentandra (CP) stem-bark.Materials and methods: The leaves of SA and CP stem-bark were extracted with methanol and the total phenolic content (TPC) of the extracts was determined and expressed as gallic acid equivalents (GAE). The extracts were evaluated for their nitric oxide scavenging activity, antioxidant activity using 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay, toxicity using brine shrimp lethality assay (BSLA) and phytochemical constituents using HPLC.Results: The TPC in SA extract was 21.26±1.29 while that of CP extract was 95.31±8.71 mg GAE. The SA and CP extracts showed antioxidant activity by DPPH with IC50 of 97.60 and 22.35 μg/mL as compared to ascorbic acid (1.4±0.34) and gallic acid (2.8±0.78) Similarly, the extracts showed nitric oxide scavenging activity of 22.50±1.3 and 5.40±0.3 µg/mL respectively compared to gallic acid with IC50 value of 1.1±0.1 µg/mL. In BSLA, SA extract had LC50 value of >1000 μg/mL while CP extract and Cyclophosphamide (standard) had LC50 value of